2020
DOI: 10.1038/s41398-020-0733-x
|View full text |Cite
|
Sign up to set email alerts
|

Essential role of microglial transforming growth factor-β1 in antidepressant actions of (R)-ketamine and the novel antidepressant TGF-β1

Abstract: In rodent models of depression, (R)-ketamine has greater potency and longer-lasting antidepressant effects than (S)ketamine; however, the precise molecular mechanisms underlying the antidepressant actions of (R)-ketamine remain unknown. Using RNA-sequencing analysis, we identified novel molecular targets that contribute to the different antidepressant effects of the two enantiomers. Either (R)-ketamine (10 mg/kg) or (S)-ketamine (10 mg/kg) was administered to susceptible mice after chronic social defeat stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 64 publications
2
53
0
1
Order By: Relevance
“…Behavioral tests, including the locomotion test, TST, FST, and 1% SPT, were performed as previously reported [ 15 , 17 – 19 , 33 – 37 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Behavioral tests, including the locomotion test, TST, FST, and 1% SPT, were performed as previously reported [ 15 , 17 – 19 , 33 – 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…The CSDS procedure was performed as previously reported [15,[17][18][19][33][34][35][36][37]. C57BL/6 mice were exposed to a different CD1 aggressor mouse for 10 min per day for 10 consecutive days (days 1-10).…”
Section: Csdsmentioning
confidence: 99%
“…Furthermore, the ability of some antidepressant drugs to induce the synthesis and the release of BDNF and TGF-β1 has been demonstrated both in vitro and in vivo studies (Caraci et al, 2010), suggesting that the long time required for BDNF restore could, at least in part, contributes to explain the therapeutic latency (2-4 weeks) of these drugs (Racagni and Popoli, 2010). Recent studies have demonstrated the rapid and long-lasting antidepressant effects of TGF-β1 as well as the key role of TGF-β1 released from microglia in mediating the antidepressant activity of (R)-ketamine (10 mg/kg) in a mouse model of depression (Zhang et al, 2020). (R)ketamine is a novel drug under study for treatment-resistant MDD patients.…”
Section: The Pathophysiology Of Depression: the Role Of Neurotrophic mentioning
confidence: 99%
“…Variations in patient baseline conditions may also have contributed to the differing results. The antidepressant effect of (R,S)-ketamine is affected by baseline inflammation levels, metabolic pathway activation levels (Ionescu et al, 2014;Zhou et al, 2020), immune status (Zhang et al, 2020), baseline depression levels (Pal et al, 2015;Stoker et al, 2019), baseline functional connectivity of the brain , family drinking history (Pennybaker et al, 2017), gender (Picard et al, 2019), and age. Moreover, (R,S)-ketamine may reduce depression scores by alleviating pain (Riddell et al, 2019;Thompson et al, 2019).…”
Section: Discussionmentioning
confidence: 99%